1982
DOI: 10.1677/joe.0.0950387
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone-dependent non-copulatory behaviour in male hamsters (Mesocricetus auratus)

Abstract: Male hamsters (intact, castrated or testosterone-treated) were tested for their response to dioestrous and to oestrous females. Response to the dioestrous female was measured in terms of proximity and olfactory investigation; response to the oestrous female was measured in terms of mounting, intromission and ejaculation. Interest in dioestrous females declined in parallel with copulatory behaviour after castration and was restored by implantation of testosterone. Six weeks of testosterone treatment failed to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1983
1983
1988
1988

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Thus 12 mm DHT (representing a ceil¬ ing dose for restoration of sniffing) was less potent than 24 mm DHT in increasing visit length, and was relatively ineffective in decreasing the time spent away from the female. We conclude that the three behav¬ ioural variables have their own separate thresholds of response to 5a-DHT, and this is consistent with the view that these components of sociosexual behaviour can be considered to be independent (Steel, 1982;Steel & Hutchison, 1986).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Thus 12 mm DHT (representing a ceil¬ ing dose for restoration of sniffing) was less potent than 24 mm DHT in increasing visit length, and was relatively ineffective in decreasing the time spent away from the female. We conclude that the three behav¬ ioural variables have their own separate thresholds of response to 5a-DHT, and this is consistent with the view that these components of sociosexual behaviour can be considered to be independent (Steel, 1982;Steel & Hutchison, 1986).…”
Section: Discussionsupporting
confidence: 87%
“…In agreement with our study of intact males, this dose level of 4-MA did not affect mean visit length, but significantly increased the mean bouts apart and decreased percentage sniffing. Castration (Steel, 1982) has short-and long-term effects. Mean visit length is markedly reduced within 2 weeks, whilst bouts away from the female lengthen slowly over 5 weeks and sniffing declines over a similar period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the discrimination between M and MM females was much greater after pre-exposure to the odour of the highly oestrogenized females. Both attraction to the female by odour and the motivation to mate with her are testosterone depend¬ ent (Gregory, Engel & Pfaff, 1975;Steel, 1982). Ex¬ tensive chemical analysis of hamster vaginal secretion and the behavioural activity of its various components (O'Connell, Singer, Pfaffman & Agosta, 1979;Singer, Macrides & Agosta, 1980) has revealed that the attrac¬ tive quality of the discharge lies in the volatile fraction and the sexually arousing quality in the macromolecular fraction (Murphy, 1973;Darby, Devor & Chorover, 1975;Singer, Macrides & Agosta, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…In a 10-min test with a female, four behavioural measures were taken: percentage of test time spent with the female; mean length of visits to the female; mean length of periods away from the female; percentage of time with the female spent sniffing or licking her. The last three of these measures vary in¬ dependently (Steel, 1982). The method of behavioural testing has been described previously (Steel, 1980(Steel, , 1984.…”
Section: Generalmentioning
confidence: 99%